Genome Sequence Analysis of Dengue Virus 1 Isolated in Key West, Florida - Shin, Dongyoung; Richards, Stephanie L.; Alto, Barry W.; Bettinardi, David J.; Smartt, Chelsea T. (My University, 2013)
Dengue virus (DENV) is transmitted to humans through the bite of mosquitoes. In November 2010, a dengue outbreak was reported in Monroe County in southern Florida (FL), including greater than 20 confirmed human cases. The virus collected from the human cases was verified as DENV serotype 1 (DENV-1) and one isolate was provided for sequence analysis. RNA was extracted from the DENV-1 isolate and was used in reverse transcription polymerase chain reaction (RT-PCR) to amplify PCR fragments to sequence. Nucleic acid primers were designed to generate overlapping PCR fragments that covered the entire genome. The DENV-1 isolate found in Key West (KW), FL was sequenced for whole genome characterization. Sequence assembly, Genbank searches, and recombination analyses were performed to verify the identity of the genome sequences and to determine percent similarity to known DENV-1 sequences. We show that the KW DENV-1 strain is 99% identical to Nicaraguan and Mexican DENV-1 strains. Phylogenetic and recombination analyses suggest that the DENV-1 isolated in KW originated from Nicaragua (NI) and the KW strain may circulate in KW. Also, recombination analysis results detected recombination events in the KW strain compared to DENV-1 strains from Puerto Rico. We evaluate the relative growth of KW strain of DENV-1 compared to other dengue viruses to determine whether the underlying genetics of the strain is associated with a replicative advantage, an important consideration since local transmission of DENV may result because domestic tourism can spread DENVs.